The Impact of Childhood Adversity on the Clinical Features of Schizophrenia. (4th August 2015) - Rajkumar, Ravi Philip
Abstract : Introduction . Recent research has drawn attention to the link between childhood maltreatment and schizophrenia. Child abuse and neglect may have an impact on symptoms and physical health in these patients. This association has not been studied to date in India. Materials and Methods . Clinically stable patients with schizophrenia (n = 62 ) were assessed for childhood adversity using the Childhood Trauma Questionnaire. The association of specific forms of adversity with symptomatology and associated variables was examined. Results . Emotional abuse was reported by 56.5% patients and physical abuse by 33.9%; scores for childhood neglect were also high. Persecutory delusions were linked to physical abuse, while anxiety was linked to emotional neglect and depression to emotional abuse and childhood neglect. Physical abuse was linked to elevated systolic blood pressure, while emotional abuse and neglect in women were linked to being overweight. Conclusions . Childhood adversity is common in schizophrenia and appears to be associated with a specific symptom profile. Certain components of the metabolic syndrome also appear to be related to childhood adversity. These results are subject to certain limitations as they are derived from remitted patients, and no control group was used for measures of childhood adversity.